2020
DOI: 10.25015/16202030742
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Rural Youth Interest in Agriculture in Sindangkasih Ciamis District

Abstract: A study on farmer regeneration has been carried out in Sindangkasih Subdistrict, Ciamis in April - July 2019 with the aim of the study: (1) to describe the extent of youth interest in agriculture, (2) find factors that influence youth interest, and (3) formulate an improvement strategy youth interest. This quantitative descriptive study involved 79 young people as respondents from 3,158 people. Data collection using a questionnaire containing closed questions in accordance with the variables and research indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 2 publications
0
9
0
2
Order By: Relevance
“…Interest is influenced by many factors, either from within a person or from outside the person. Effendy, Maryani, and Yulia [5] reported that the youngster's interest in agriculture was influenced by many factors, such as the desire to receive awards, desire to have an achievement, life necessities, extension activities, resource availability, and government program support. Similarly [10] on farmers' interest in jajar legowo system application concluded that interest was determined by the farmer characteristics, including age, education level, land ownership area, and farming experience, while external factors were available facilities and infrastructure support and easier access to gain information and technology sources.…”
Section: Thinking Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Interest is influenced by many factors, either from within a person or from outside the person. Effendy, Maryani, and Yulia [5] reported that the youngster's interest in agriculture was influenced by many factors, such as the desire to receive awards, desire to have an achievement, life necessities, extension activities, resource availability, and government program support. Similarly [10] on farmers' interest in jajar legowo system application concluded that interest was determined by the farmer characteristics, including age, education level, land ownership area, and farming experience, while external factors were available facilities and infrastructure support and easier access to gain information and technology sources.…”
Section: Thinking Frameworkmentioning
confidence: 99%
“…The land area owned by respondents in Tarogong Kidul District was relatively in a large category around 15,000 -25,000 m. However, there were also respondents who only had a narrow land area less than 10,000 m and some of whom only had a 50-m land area ownership. Similarly [5] mentioned that the agricultural land area influenced the farmer participation to improve the group capabilities. When the farmer ability increases, the farmer's interest will also increase.…”
Section: Variable Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…07/Permentan/OT.140/1/2013 concerning Guidelines for the Development of Generation of the Young Agricultural Entrepreneurs (Young Farmers). The next few programs are the growth and development of young agricultural entrepreneurs that have been carried out in the last few years, such as the report from Anwarudin et al (2020c) and Effendy et al (2020). The program is rolled out based on Decree of the Minister of Agriculture of the Republic of Indonesia Number 10/Kpts/SM.210/I/05/2019 concerning Guidelines for the Growth of Young Agricultural Entrepreneurs.…”
Section: Factors Affecting the Interest Of Young Agricultural Entrepreneurs (Young Farmers)mentioning
confidence: 99%
“…The declining interest of youth to work in the agricultural sector is one of the critical problems being faced in developing the agricultural sector in Indonesia, causing the regeneration of agricultural human resources not to work well [6]. The research revealed that the lack of youth participation in agricultural activities was caused by a lack of technical knowledge and experience in agriculture [7]. Whereas the sustainability of the farm requires the role of all parties and integrase between agricultural lines both on-farm and off-farm [8].…”
Section: Introductionmentioning
confidence: 99%